Educação linguística e formação de professores de línguas crítico-reflexivos: uma análise dos discursos de licenciandos do curso de letras da UEVA - Lins Júnior, José Raymundo Figueiredo (2019)
The research aims to analyze the teacher training of language teachers for a project of language education in basic education. This is a study in Applied Linguistics, which is based on the relationship between linguistic knowledge and language teaching, as the process of developing language awareness. The study, with an interpretative approach, presents a corpus of students' speeches, at their last semesters in the Course of Letters, at Universidade Estadual Vale do Acaraú. The discourse analysis is based on the transitivity system of Systemic-Functional Grammar (HALLIDAY and MATTHIESSEN, 2004) and related to the ideologemas (DEL VALLE, 2010) identified in the Political Educational Project of the UEVA Letters course, stating the need of attention for the linguistic education project in basic education (BAGNO; RANGEL, 2005) through the perspectives of educational sociolinguistics (BORTONI-RICARDO, 2005) for language teaching. Finally, I state that the language awareness of the language teachers is a professional knowledge, which is manifested through critical reflexive positions on language and grammar, as well as the relation of this knowledge with the teaching of languages, represented by speakers’ lexicogrammatical choices influenced by the curricular guidelines and teaching practices of the teachers in training.